2015
DOI: 10.1152/japplphysiol.00460.2015
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps exercise intolerance in patients with chronic obstructive pulmonary disease: the potential role of altered skeletal muscle mitochondrial respiration

Abstract: This study sought to determine if qualitative alterations in skeletal muscle mitochondrial respiration, associated with decreased mitochondrial efficiency, contribute to exercise intolerance in patients with chronic obstructive pulmonary disease (COPD). Using permeabilized muscle fibers from the vastus lateralis of 13 patients with COPD and 12 healthy controls, complex I (CI) and complex II (CII)-driven State 3 mitochondrial respiration were measured separately (State 3:CI and State 3:CII) and in combination (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 34 publications
6
35
0
Order By: Relevance
“…Quadriceps muscle citrate synthase activity, an index of mitochondrial capacity, was not different between controls and patients with COPD (Richardson et al 2004). Estimation of peak quadriceps muscle O 2 utilization (Gifford et al 2016), from in vitro mitochondrial respiration data, in patients with COPD is markedly greater (>0.40 l min −1 ) than theV MO 2 peak in the current patients with COPD (Gifford et al 2015(Gifford et al , 2017. Peak work load was 25% greater during KE in hyperoxia (100% O 2 ) compared to normoxia in patients with COPD (Richardson et al 1999).…”
Section: Muscle Diffusive O 2 Transportmentioning
confidence: 68%
“…Quadriceps muscle citrate synthase activity, an index of mitochondrial capacity, was not different between controls and patients with COPD (Richardson et al 2004). Estimation of peak quadriceps muscle O 2 utilization (Gifford et al 2016), from in vitro mitochondrial respiration data, in patients with COPD is markedly greater (>0.40 l min −1 ) than theV MO 2 peak in the current patients with COPD (Gifford et al 2015(Gifford et al , 2017. Peak work load was 25% greater during KE in hyperoxia (100% O 2 ) compared to normoxia in patients with COPD (Richardson et al 1999).…”
Section: Muscle Diffusive O 2 Transportmentioning
confidence: 68%
“…Several studies found that sarcopenia is more common in patients with COPD than in matched healthy controls 6971. In addition, adults with COPD exhibit skeletal muscle dysfunction at the biochemical, cellular, and structural levels 72,73. Finally, as the severity of COPD and the concomitant dyspnea worsens, patients can experience decrease in muscle strength, impaired mobility, sarcopenia, and ultimately, frailty.…”
Section: Sarcopeniamentioning
confidence: 99%
“…Because of identical spectral characteristics, Hb and myoglobin (Mb) are not separated using NIRS. However, although still somewhat contentious (14), the signal is usually considered to be derived mainly from Hb (30). Changes in microvascular oxygenation of the calf muscle were continuously monitored at 2 Hz using a near infrared frequency resolved spectroscopy oximeter (Oxiplex TS; ISS, Champaign, IL).…”
Section: Subjectsmentioning
confidence: 99%